Echinoderm diversity of a tropical estuary in the largest river basin of the Costa Rican Pacific, Eastern Tropical Pacific - Azofeifa Solano, Juan Carlos (2017)
Echinoderms within the Eastern Tropical Pacific have mainly been studied in association with coral reefs. Investigations on echinoderms associated with soft-bottoms and estuaries are still scarce. The present study reports on the echinoderm species inhabiting the soft-bottom sediments of shallow-brackish waters adjacent to the largest river basin along the Pacific coast of Costa Rica, Térraba-Sierpe wetland. Nine species were recorded, three of them new records for Costa Rica: Luidia columbia, L. latiradiata, and L. superba. The most common species were L. columbia, Astropecten armatus, A. regalis, and L. latiradiata. This contributes towards current knowledge on the biodiversity of Térraba-Sierpe wetland and should be considered as a baseline upon which to monitor the effects of future impacts on this important mangrove area.